Reliability Impact Of Dynamic Thermal Rating System On Power System - Lai, Lik Chin (Universiti Sains Malaysia, 2017)
Conventionally, generation of electrical energy comes with a large amount of carbon dioxide emission. The unceasing construction of power plant to meet the demand due to industrialization and urbanization will inexorably lead to climate change. To mitigate the crisis, the current electrical technology has to keep pace with the advancement of smart grid technology.Smart grid technology can be defined as the power grid that can detect and react to local changes and allow two-way communication between the utility company and the grid. This thesis begins by providing the research background that includes structural of the power system, the method of power system analysis and power system reliability in chapter 1. Next, IEEE 738 standard, Monte Carlo simulation and Optimum power flow analysis have been reviewed in chapter 2. In chapter 3, the methodology used in this thesis is explained in detail such as sequential Monte Carlo simulation, reliability impact of Dynamic Thermal Rating system(DTR) and sensitivity analysis for DTR system. Thereafter, the analyses are performed by using the proposed methodology and proved that DTR system is able to improve the reliability of power system by reducing Expected Energy Not Served (EENS). Furthermore, it was found that Reliability Test Network(RTN) reliability indices are normally not sensitive toward the reliability of the DTR system. Lastly, a conclusion is made and future work is suggested in chapter 5